Incarcerated Amyand’s hernia: a case report and literature review - Domingues, Joana C.; Mineiro, José F. (International Surgery Journal, 2025)
While inguinal hernias are among the most common surgical conditions, an Amyand’s hernia, defined by the presence of the appendix within an inguinal hernia sac, is a rare clinical entity. A case of a 92-year-old woman who presented to the emergency department with two days of abdominal pain and a non-reducible right inguinal mass compatible with an incarcerated hernia. Emergency surgery revealed an inflamed appendix within the hernia sac; appendectomy and hernia repair using the Lichtenstein technique were performed, resulting in an uneventful recovery. Amyand’s hernia is often asymptomatic and usually diagnosed incidentally during surgery, whether elective or emergent in case of incarcerated or strangulated hernia. Acute appendicitis may be present and increases the risk of complications. Management depends on the appendix’s inflammatory state and hernia complexity, typically involving appendectomy and hernia repair. Various classification systems provide guidance to treatment however surgical decisions should be tailored to patient-specific factors and surgeon expertise. More studies are needed in order to establish guidelines.